Sclera and Iris Color Interact to Influence Gaze Perception - Yorzinski, Jessica L.; Thorstenson, Christopher A.; Nguyen, Trezze P. (Frontiers in Psychology, 2021)
The white sclera is important in facilitating gaze perception in humans. Iris color may likewise influence gaze perception but no previous studies have directly assessed its effect. We therefore examined how the interaction between sclera and iris color influences human gaze perception. We recorded the eye movements of human participants as they performed a visual search task with human faces exhibiting directed or averted gaze. The faces either exhibited light or dark irises. In addition, the faces had sclera that were depigmented (white) or pigmented (matched the color of the iris). We found that participants were quick and accurate in evaluating gaze regardless of iris color in faces with depigmented sclera. When the sclera were pigmented, participants were slower to evaluate the gaze of faces with both light and dark irises but these effects were most pronounced in the faces with dark irises. Furthermore, participants were generally less accurate in assessing faces with pigmented sclera when the irises were dark rather than light. Our results suggest that depigmented sclera are especially important for gaze perception in faces with dark irises. Because depigmented sclera likely evolved at a time when ancestral humans exhibited dark irises, the depigmented sclera may have been crucial for efficient and accurate gaze perception in ancestral humans.